Risk Management and Its Influence on Corporate Performance: A Systematic Literature Review Approach - Deni Sunaryo; Yoga Adiyanto; Ega Violita; Fatin Nabila; Killah Eneng Killah (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Objective: This study investigates the critical role of risk management practices in enhancing corporate performance, with a specific focus on financial institutions and manufacturing sectors. The research aims to uncover how effective risk management contributes to organizational resilience, operational efficiency, and long-term sustainability.Methodology: A Systematic Literature Review (SLR) methodology was employed to analyze 11 peer-reviewed academic articles published between 2015 and 2023. The selected studies were drawn from reputable databases such as Scopus and Web of Science, using predefined inclusion criteria. The analysis focused on identifying patterns, gaps, and emerging trends in risk management practices.Findings: The study reveals that robust risk management significantly enhances organizational resilience, mitigates exposure to financial and operational risks, and fosters improved corporate governance. Frameworks such as ISO 31000 and Enterprise Risk Management (ERM) are identified as pivotal in aligning risk management with strategic objectives, thereby driving sustainable growth.Contribution: This research underscores the need for a unified and standardized risk management framework that addresses sector-specific challenges while promoting cross-industry applicability. Policymakers and industry leaders are urged to prioritize risk management as a strategic imperative, especially in times of crisis.